The Implementation of Social Business Model Canvas on Mie Qta - Kathleen, Sabrina; Fauziyah, Azizah; Kanita, Ghia Ghaida (Universitas Pendidikan Indonesia, 2021)
The purpose of this study was to to find out how to implement the social business model for the Mie Qta business. Mie Qta is a business in the FB (food and beverage) industry that has been established since 2018 and is located in the South Tangerang Region. Mie Qta's initial business model is a general business model that has been widely used by other businesses. Mid-2020 Mie Qta began to remodel its business model into a social business model that started with a collaboration with one of the fundraiser communities in Jakarta (Goodsforgood) to raise funds for medical personnel treating COVID-19 victims. Seeing the planning of Mie Qta in implementing the Social Business Model Canvas, it is necessary to do research on the social business model that aims to find out how to implement the social business model for the Mie Qta business.